Coverage index of various communication platforms: a segmented approach to philippine university marketing - Dagumboy, Eloida Carpio (Jurnal Studi Komunikasi, 2019)
The digital era has ushered the rise in the utilisation of alternative communication platforms in integrated marketing communications (IMC). The contemporary business environment necessitates employing high-yield communication platforms to help sustain and further an institution’s position in the industry. This paper aims to identify the most efficient platforms employed by the university, accounting the preference of the target audience and the platform’s actual reach through a gauge termed coverage index (CI). Results from net 303 valid responses, gathered via an online survey, show that the following in descending arrangement: relatives/friends, open house, social media, and university website are in the upper quartile (CI>67.78%). Further, variance analysis uncovered differences in the preference and reach ratings of certain platforms when respondents are classified according to demographic characteristics. Universities then can strategize their IMC applying high CI platforms. Additionally, the segmented approach to marketing can be incorporated depending on the prospective students’ profile.